PARAPHRASES FORMED IN THE PUBLIC CONSCIOUSNESS - Aigul Baydebekkyzy Amirbekova; Аnar Fazylzhan Muratkyzy (International Journal of Innovative Technologies in Social Science, 2019)
The article deals with the cognitive-pragmatic potential of a new paraphrase, a language instrument that influences the public consciousness. The purpose of the article is to preserve the depth of use of the new paraphrase in people’s memory and to identify the reasons for its widespread use. The strength of manipulative, pragmatic actions in the content of imaginative, random applications that change the opinion of society is confirmed by successive examples. The reasons for the transfer of new usage in modern media in the paraphrase, metonymic paraphrase, metaphor, occasional paraphrase will be revealed. As public opinion grows, changes in public consciousness can be observed. The article says that only accurately describing the stereotypical ideas of people about the knowledge of the world can affect the public consciousness. The article uses linguocognitive, lingvo-semantic, semantic methods of analysis.